Konseptualisasi Video Animasi Pembelajaran Akidah Akhlak pada Materi Perilaku Terpuji Menggunakan Aplikasi Canva - Khansa Qadisiyya; Nurmawati (YASIN, 2026)
Although the use of the Canva application as a learning medium has been widely studied, research specifically examining the conceptual design of animated learning videos for Akidah Akhlak on the topic of Praiseworthy Conduct remains relatively limited. This study aimed to analyse media needs and develop a conceptual design for an animated Akidah Akhlak learning video on the topic of Praiseworthy Conduct using the Canva application. This study employed a qualitative approach with a descriptive design and involved two teachers and two students selected using purposive sampling. Data were collected through interviews, observations, and documentation and were subsequently analysed using the interactive model of Miles, Huberman, and Saldaña, which comprises data reduction, data presentation, and conclusion drawing. The results showed that the learning media used had not fully met students’ learning needs because they remained limited in presenting the material in an engaging, concrete, and interactive manner. Based on the needs analysis, the conceptual design of the animated video was developed around six main components: content on Praiseworthy Conduct, an engaging visual design, the use of simple language, contextual presentation of the material, a short video duration, and the use of the Canva application as a development medium. This study confirms that needs analysis is an important foundation for designing learning media that align with students’ characteristics and learning objectives. These findings provide a conceptual contribution to the development of learning media for Islamic Religious Education and practical implications for teachers and researchers in developing animated videos based on user needs. Future research should develop the conceptual design into a learning media product and assess its validity, practicality, and effectiveness.